Management of Helicobacter pylori Infection: Current Standards and Future Perspectives - Marszałek, Dominika; Czudowska, Michalina; Zawadzka , Magdalena; Kurzątkowska, Klaudia; Bystros, Aleksandra; Drozdowska, Marta; Borychowska , Emilia; Ocimek, Aleksandra; Gwóźdź, Karolina; Mierzejewska, Zofia (Journal of Education, Health and Sport, 2026)
Helicobacter pylori infection remains a major clinical challenge due to its high global prevalence, rising antibiotic resistance, and the increasingly limited effectiveness of traditional treatment approaches. Although several diagnostic and therapeutic strategies are well established, eradication rates continue to decline in many regions. Effective management now requires careful selection of treatment based on local resistance patterns, adequate acid suppression, and attention to treatment adherence. Current guidelines support the use of bismuth-containing quadruple therapy, concomitant therapy, and susceptibility-guided approaches where available. Emerging treatment options—including potassium-competitive acid blockers, rifabutin-containing therapies, antimicrobial peptides, microbiome-modulating interventions, and vaccine candidates—show promising potential to improve future outcomes. Continued progress in diagnostics and access to newer therapies may enable more individualized, effective, and preventive strategies in the management of H. pylori infection.